2014
DOI: 10.1016/j.afjem.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Essentials for emergency care: Lessons from an inventory assessment of an emergency centre in Sub-Saharan Africa

Abstract: Introduction:The World Health Organization (WHO) has published lists of essential equipment and supplies for delivering emergency care in resource-limited settings. The objective of this study was to assess material resources available for adult emergency care at a major academic tertiary care referral centre in Accra, Ghana, to determine quality improvement needs. Methods: A spot inventory of emergency centre equipment and supplies was conducted in Korle-Bu Teaching Hospital (KBTH) and compared to the WHO ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The WHO provide checklists for very basic equipment and emergency room capacity under their Integrated Management for Emergency and Essential Surgical Care toolkit [45], which have been used to provide basic information about emergency care capacity in a centre in Sub-Saharan Africa [46]. Current WHO work in Emergency and Trauma Care provides a country-level EC Systems Assessment (ECSA) tool, implemented through a facilitated multi-stakeholder process that aids national policy and planning for EC improvement [47].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO provide checklists for very basic equipment and emergency room capacity under their Integrated Management for Emergency and Essential Surgical Care toolkit [45], which have been used to provide basic information about emergency care capacity in a centre in Sub-Saharan Africa [46]. Current WHO work in Emergency and Trauma Care provides a country-level EC Systems Assessment (ECSA) tool, implemented through a facilitated multi-stakeholder process that aids national policy and planning for EC improvement [47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that educational interventions for paramedics are less effective if equipment availability limits their ability to implement their knowledge [19]. Financial and supply‐chain barriers often hinder the ability to adopt intervention strategies and provide quality emergency care [20].…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…7 It directly accounts for a significant portion of stock-outs in Sub-Saharan Africa, resulting in demand seasonality and facility access disruptions, as well as causing increased morbidity and mortality. 4,[8][9][10][11][12][13] The scenario worsens in developing nations as their drug spending account for 60% to 80% of population expenditures and up to 90% of people buy drugs out-of-pocket. In Ethiopia where the government is the main source of drug supply and their access to population is ensured majorly through direct out-of-pocket payment, poor inventory management stifles financial resources, leads to an increase in out-of-pocket spending, and, as a result, a decline in the quality of healthcare services.…”
Section: Introductionmentioning
confidence: 99%